PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS V MELALUI STRATEGI PEMBELAJARAN KWL (KNOW, WANT TO KNOW LEARNED) DI UPT SD NEGERI 159 MULYOREJO I: Penelitian Tindakan Kelas - Rania Naswa Nurillahi; Maria Ulviani; Abdul Munir Kandongan (STKIP Subang, 2025)
This classroom action research aims to improve the reading comprehension skills of fifth-grade students at UPT SD Negeri 159 Mulyorejo I through the application of the KWL (Know, Want to Know, Learned) learning strategy. The study was conducted collaboratively between researchers and the class teacher using the Kemmis and McTaggart model, which includes stages of planning, action, observation, and reflection across two learning cycles. The research subjects were 41 students in the 2024/2025 academic year. Data collection techniques included observation, written tests, and documentation, analyzed both qualitatively and quantitatively. In the first cycle, only 22 students (53.66%) achieved the minimum mastery criterion (KKM) with an average score of 64.88. After implementing improvements in the second cycle, student performance increased significantly, with 35 students (85.37%) reaching mastery and an average score of 82.68. The implementation of the KWL strategy proved to be effective in activating students’ prior knowledge, fostering curiosity, and facilitating reflection on what they learned from the texts. The study concluded that the KWL strategy successfully improved reading comprehension outcomes and is recommended for continued use in Indonesian language learning to enhance literacy skills in elementary education.